2018
DOI: 10.17776/csj.434265
|View full text |Cite
|
Sign up to set email alerts
|

Quaternary Adsorption Effect of Nickel (II), Antimony (III), Manganese (II) and Copper (II) onto Living Two Green Microalgae

Abstract: This study aimed to investigate Ni, Sb, Mn and Cu adsorption from aqueous solution by Chlorella and Scenedesmus algae. The competitive adsorption efficiency of nickel (Ni 2+), antimony (Sb 3+), manganese (Mn 2+) and copper (Cu 2+) onto two living microalgae strains was studied from multi-metal aqueous solution for 24h incubation time. After exposure, chlorophyll a-b, total carbohydrate and Atomic force microscopy (AFM) imaging were performed. Then adsorption isotherms models of metal ions were determined based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Considering the results of their study, Şentürk & Yıldız, (2018b) revealed that Chlorella and Scenedesmus cells are effective adsorbents in removing four heavy metals, especially Cu + 2 ions from aqueous solutions, due to the high efficiency of Cu adsorption. The results of these reports were found to be consistent with the findings obtained in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the results of their study, Şentürk & Yıldız, (2018b) revealed that Chlorella and Scenedesmus cells are effective adsorbents in removing four heavy metals, especially Cu + 2 ions from aqueous solutions, due to the high efficiency of Cu adsorption. The results of these reports were found to be consistent with the findings obtained in our study.…”
Section: Discussionmentioning
confidence: 99%